2015
DOI: 10.1039/c4cp05678g
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation dynamics in dissociative electron attachment to CO probed by velocity slice imaging

Abstract: Complete dissociation dynamics in electron attachment to carbon monoxide (CO) have been studied using the newly developed velocity slice imaging (VSI) technique. Both kinetic energy and angular distributions of O(-) ions formed by dissociative electron attachment (DEA) to CO molecules have been measured for 9, 9.5, 10, 10.5, 11, and 11.5 eV incident electron energies around the resonance. Detailed observations conclusively show that two separate DEA reactions lead to the formation of O(-) ions in the ground (2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 35 publications
4
31
2
Order By: Relevance
“…The DEA experiments suggest that there are two 2 Σ + resonances between 10 eV and 11 eV [17][18][19][20][21][22][23]. Our calculations detected only a single 2 Σ + resonance at 12.9 eV.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The DEA experiments suggest that there are two 2 Σ + resonances between 10 eV and 11 eV [17][18][19][20][21][22][23]. Our calculations detected only a single 2 Σ + resonance at 12.9 eV.…”
Section: Discussionmentioning
confidence: 52%
“…More recently, experimental DEA studies were undertaken by Nag and Nandy [23] and Tian et al [24]. These studies proved somewhat controversial regarding the nature of the resonances involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one angular distribution measurement over limited angular range by Hall et al [5] concluded a TNI state with Π symmetry is responsible for both the processes. In the recent times, the momentum imaging techniques [6,7,8] have been used to understand the complete dynamics in DEA to CO molecule.…”
mentioning
confidence: 99%
“…The authors introduced coherent interference The electron beam direction is from left to right and passing through the centre of the images. Graphs have been taken from [7].…”
mentioning
confidence: 99%